2015
DOI: 10.1007/s12275-015-5432-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses in Streptococcus species and their effects on the host

Abstract: Streptococci cause a variety of diseases, such as dental caries, pharyngitis, meningitis, pneumonia, bacteremia, endocarditis, erysipelas, and necrotizing fasciitis. The natural niche of this genus of bacteria ranges from the mouth and nasopharynx to the skin, indicating that the bacteria will inevitably be subjected to environmental changes during invasion into the host, where it is exposed to the host immune system. Thus, the Streptococcus-host interaction determines whether bacteria are cleared by the host'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…31,32 Although not well understood, several underlying mechanisms have been proposed: the release of inflammatory mediators (interleukin-1α and -1β and tumor necrosis factor-α) into the circulation that play key role in atherogenesis 33 results in macrophage stimulation by the lipopolysaccharides of these microorganisms, 34 enhancing platelet aggregation and thereby increasing the risk of thrombosis, 35 triggering host stress responses in endothelial cells. 36 The number of teeth with caries was associated with increased MetS risk in univariate analysis, and remained statistically significant despite the fact that the effect size was attenuated after adjustment for explanatory variables. Supporting our results, a recent study has shown that the number of teeth with caries and systemic exposure to A. actinomycetemcomitans are associated with several components of MetS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…31,32 Although not well understood, several underlying mechanisms have been proposed: the release of inflammatory mediators (interleukin-1α and -1β and tumor necrosis factor-α) into the circulation that play key role in atherogenesis 33 results in macrophage stimulation by the lipopolysaccharides of these microorganisms, 34 enhancing platelet aggregation and thereby increasing the risk of thrombosis, 35 triggering host stress responses in endothelial cells. 36 The number of teeth with caries was associated with increased MetS risk in univariate analysis, and remained statistically significant despite the fact that the effect size was attenuated after adjustment for explanatory variables. Supporting our results, a recent study has shown that the number of teeth with caries and systemic exposure to A. actinomycetemcomitans are associated with several components of MetS.…”
Section: Discussionmentioning
confidence: 89%
“…Endogenous bacteria (most prominently Streptococcus mutans and Streptococcus sobrinus, as well as lactobacilli) in the biofilm produce weak organic acids as a byproduct of the metabolism of fermentable carbohydrates. 36 The number of teeth with caries was associated with increased MetS risk in univariate analysis, and remained 30 One explanation for this association may be that the number of teeth with caries is a surrogate marker for the lifetime accumulation of oral infections. Over recent decades, accumulating epidemiologic data indicate that common oral diseases, such as caries, periodontal diseases, and the loss of teeth, are associated with MetS, cardiovascular diseases, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, heat shock proteins (HSPs) play crucial roles in protecting cells against environmental stresses, such as heat shock, low serum, chemicals, and pathogenic bacteria. 3,4 Among the HSP family, the 70 kDa HSPs are the most responsible for intracellular chaperone and extracellular immunoregulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…T o survive in diverse environments, bacteria must sense and respond to external stimuli. Two-component signaling systems (TCSs) are ubiquitous in prokaryotes and represent a major mechanism through which bacterial cells adapt to environmental changes (1,2). A typical TCS consists of a membrane-bound sensor histidine kinase (HK) and a cytoplasmic response regulator (RR) (1).…”
mentioning
confidence: 99%
“…Once the mucosal barriers are breached, the bacteria disseminate to different organs and tissues by the bloodstream. TCSs are usually employed to sense and respond to extracellular signals during the infection process (2,9). Bioinformatics analysis of the genome of SS2 strains identified 15 TCSs (10), among which RevS, Salk/SalR, CovR, CiaRH, Ihk/Irr, VirR/VirS, NisK/NisR, 1910HK/RR, and VraSR SS have been reported to regulate the expression of putative virulence factors, mediate multidrug resistance, or alter bacterial metabolism (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), thereby contributing to the adaption of SS2 strains to environmental stimuli.…”
mentioning
confidence: 99%